2014
DOI: 10.3892/or.2014.3143
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neonatal Nav1.5 in human brain astrocytoma and its effect on proliferation, invasion and apoptosis of astrocytoma cells

Abstract: Abstract. In the present study, we designed and conducted a series of assays to determine the expression of voltage-gated sodium channel (VGSC) neonatal isoform Nav1.5 (nNav1.5) in human brain astrocytoma and its effect on the proliferation, migration, invasion and apoptosis of astrocytoma U251 cells. The results showed that nNav1.5 mRNA and protein were expressed in both human brain astrocytoma and normal brain tissues, but their expression levels in astrocytoma were significantly higher (P<0.05). In astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
5
33
0
Order By: Relevance
“…Previous studies showed that VGSCs control tumor growth and metastasis, and tumor cell invasion but not proliferation in non‐small cell lung cancer, breast cancer, colon cancer and cervical cancer . However, other reports indicate that VGSCs control cell invasion as well as proliferation in astrocytoma and prostate cancer, which is consistent with our results. Here, we shed light on the role of Na v 1.7 in promoting both invasion and proliferation of GC cells, which may be due to the specificity of different cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that VGSCs control tumor growth and metastasis, and tumor cell invasion but not proliferation in non‐small cell lung cancer, breast cancer, colon cancer and cervical cancer . However, other reports indicate that VGSCs control cell invasion as well as proliferation in astrocytoma and prostate cancer, which is consistent with our results. Here, we shed light on the role of Na v 1.7 in promoting both invasion and proliferation of GC cells, which may be due to the specificity of different cancers.…”
Section: Discussionsupporting
confidence: 92%
“…However, the present study, in accordance with data from previous studies, demonstrated that Nav1.5 was expressed in various mammalian tissues including the brain, neuronal cell lines (214), dorsal root ganglia (DRG) (1517), gastrointestinal tract (18), and various tumor tissues and cell lines (1932), in addition to its established presence in cardiac tissue. Currently, a total of nine distinct Nav1.5 channel isoforms, Nav1.5a-f and the truncated variants Nav1.5 E28B-D, have been identified.…”
Section: Introductionsupporting
confidence: 92%
“…Therefore, the present study, in accordance with previous studies, selected the terminology ‘Nav1.5e’ rather than ‘neonatal Nav1.5’ to describe this splicing variant in normal tissues. Conversely, numerous authors decide to use the terminology ‘neonatal Nav1.5’ when investigating the expression of Nav1.5 in tumor cell lines (8,23,27,29,32), as ‘neonatal’ is there used to represent the re-expression of an embryonic gene or oncogene and its expression is associated with the occurrence and development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the anti-ELTD1 treatment worked to down-regulate SCN5A, TRPM8 and BMP2, which were all shown to increase glioma cell proliferation, migration and invasion [48][49][50]. Therefore, suggesting that ELTD1 has a more complex relationship with Notch1 than previously understood.…”
mentioning
confidence: 90%